1970
DOI: 10.1002/pol.1970.160080507
|View full text |Cite
|
Sign up to set email alerts
|

Nature of DC conductivity in polyamides

Abstract: The dc conductivity of poly(sebacyl piperazine), a polyamide prepared from the secondary diamine piperazine, in which no NH groups are present and no hydrogen bonding can occur, has been examined and compared with that of a normal 610 polyamide. The results obtained point clearly to the conduction in the 610 polyamide being electronic below about 100°C but probably involving protons as well as electrons above this temperature. This is largely consistent with the findings of earlier work and clarifies the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Many polymeric materials have a resistivity higher than this threshold value [14], possibly by some orders of magnitude. For example, a resistivity of 1 × 10 15  cm has been reported for a dry nylon film [15]. All the results presented in the following sections were obtained by assuming  c = 2 × 10 11  cm, as in our previous study [7] and in other studies [16].…”
mentioning
confidence: 83%
“…Many polymeric materials have a resistivity higher than this threshold value [14], possibly by some orders of magnitude. For example, a resistivity of 1 × 10 15  cm has been reported for a dry nylon film [15]. All the results presented in the following sections were obtained by assuming  c = 2 × 10 11  cm, as in our previous study [7] and in other studies [16].…”
mentioning
confidence: 83%
“…4,7 These results indicate that neither the trunk molecular-mass impurities in the film. 3,15 polymer nor the grafted one and nor graft copolymer metal complex has a strongly crystalline Optical Gap Measurements structure.…”
Section: Xrd Investigationmentioning
confidence: 98%
“…Bavid [70] measured the d.c. conductivity in poly(sebacyl piperazine) and compared the results with a for Nylon 6-10. It was indicated that the conductivity in the 6-10 polyamide was electronic at temperatures below 100°C, but involved protons above 100°C, similar to Sacher's results on poly(ethylene terephthalate) referred to above [66] .…”
Section: A Solidsmentioning
confidence: 99%